A Detailed Protocol for Subcellular RNA Sequencing (subRNA‐seq). Issue 1 (13th February 2018) - Mayer, Andreas; Churchman, L. Stirling
Abstract: In eukaryotic cells, RNAs at various maturation and processing levels are distributed across cellular compartments. The standard approach to determine transcript abundance and identity in vivo is RNA sequencing (RNA‐seq). RNA‐seq relies on RNA isolation from whole‐cell lysates and thus mainly captures fully processed, stable, and more abundant cytoplasmic RNAs over nascent, unstable, and nuclear RNAs. Here, we provide a step‐by‐step protocol for subcellular RNA‐seq (subRNA‐seq). subRNA‐seq allows the quantitative measurement of RNA polymerase II–generated RNAs from the chromatin, nucleoplasm, and cytoplasm of mammalian cells. This approach relies on cell fractionation prior to RNA isolation and sequencing library preparation. High‐throughput sequencing of the subcellular RNAs can then be used to reveal the identity, abundance, and subcellular distribution of transcripts, thus providing insights into RNA processing and maturation. Deep sequencing of the chromatin‐associated RNAs further offers the opportunity to study nascent RNAs. Subcellular RNA‐seq libraries are obtained within 5 days. © 2017 by John Wiley & Sons, Inc.